Linked Hospital and Primary Care Database Analysis of the Incidence and Impact of Psychiatric Morbidity Following Gastrointestinal Cancer Surgery in England. Issue 1 (July 2016) - Bouras, George; Markar, Sheraz R.; Burns, Elaine M.; Mackenzie, Hugh A.; Bottle, Alex; Athanasiou, Thanos; Hanna, George B.; Darzi, Ara
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To evaluate risk of psychiatric morbidity and its impact on survival in gastrointestinal surgery. Background: Psychiatric morbidity related to surgery is poorly understood, and may be evaluated using linked hospital and primary care data. Methods: Patients undergoing gastrointestinal surgery from 2000 to 2011 with linkage of Clinical Practice Research Datalink (CPRD), Hospital Episodes Statistics (HES), Office of National Statistics (ONS), and National Cancer Intelligence Network (NCIN) databases were studied. Psychiatric morbidity was defined as a diagnosis code in CPRD or HES, or a prescription code for psychiatric medication in the 36 months before (preoperative) or 12 months after (postoperative) surgery. Newly diagnosed psychiatric morbidity was measured in patients without preoperative psychiatric morbidity. Results: In our study, 14, 797 (23.8%) and 47, 279 (76.2%) patients had surgery for cancer and benign disease, respectively. Postoperative psychiatric morbidity was observed in 10.1% (1500/14797) of patients undergoing cancer surgery. Logistic regression revealed that when adjusted for other factors, cancer diagnosis [odds ratio (OR) = 1.19] independently predicted postoperative psychiatric morbidity ( P  < 0.05). Hepatopancreaticobiliary resection (OR = 2.40) and esophagogastrectomy (OR = 2.55) carried the highest risks of postoperative psychiatric morbidity ( P  < 0.05). Preoperative psychiatric morbidity (OR = 1.16) and newly diagnosed psychiatric morbidity (OR = 1.87) were associated with increased 1-year mortality in cancer patients only ( P  < 0.05). Conclusions: Postoperative psychiatric morbidity affected a tenth of patients who underwent gastrointestinal cancer surgery and was associated with increased mortality. Strategies to identify patients at risk preoperatively and to reduce the observed adverse impact of postoperative psychiatric morbidity should be part of perioperative care in complex cancer patients.